An empirical analysis of the influence of financialization on investment in Russia - Dmitry S. Tretyakov (Voprosy Ekonomiki, 2021)
This paper tries to estimate the impact of financialization on fixed investment in Russia. The work is carried out by using panel data based on reports of non-financial publicly listed companies for 1999–2019. The study finds that financial expenses aimed at paying interest on external financing and paying dividends — that is, focusing on shareholder value, and hence decreasing the internal funds of companies, reduce real investments. Financial incomes have shown the crowding-out effect for large companies. Financial incomes as additional “free” funds in large companies are not perceived as an opportunity to accumulate fixed assets. Managers prefer to increase financial investments instead of real ones. In small and medium-sized companies, financial incomes, however, drive the growth of physical investment. This is because small firms, at a particular stage in their lives, find it more profitable to invest in their own growth. The results from the general sample, without dividing by size, indicate that financialization in Russia clearly reduces real investment.